2002
DOI: 10.1093/genetics/160.2.481
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans lin-45 raf Is Essential for Larval Viability, Fertility and the Induction of Vulval Cell Fates

Abstract: The protein kinase Raf is an important signaling protein. Raf activation is initiated by an interaction with GTP-bound Ras, and Raf functions in signal transmission by phosphorylating and activating a mitogen-activated protein (MAP) kinase kinase named MEK. We identified 13 mutations in the Caenorhabditis elegans lin-45 raf gene by screening for hermaphrodites with abnormal vulval formation or germline function. Weak, intermediate, and strong loss-of-function or null mutations were isolated. The phenotype caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…To better understand how mutations in the DTS increase LIN-45(S312A) activity, we tested for Ras dependence by introducing mutations in the LIN-45 RBD that prevent Ras binding. Residues Q95 and R118 of the LIN-45 RBD correspond to Q66 and R89 of RAF1, sites that are required for interaction with Ras-GTP and plasma membrane recruitment (BLOCK et al 1996;HSU et al 2002;HARDING et al 2003). We previously showed that transgenes expressing YFP-LIN-45(Q95A, R118A) fail to rescue the lin-45 null mutant, consistent with a loss of function (TOWNLEY et al 2023).…”
Section: Lin-45(s312a) Signaling Is Dependent On Ras and Ksr Activitymentioning
confidence: 85%
See 1 more Smart Citation
“…To better understand how mutations in the DTS increase LIN-45(S312A) activity, we tested for Ras dependence by introducing mutations in the LIN-45 RBD that prevent Ras binding. Residues Q95 and R118 of the LIN-45 RBD correspond to Q66 and R89 of RAF1, sites that are required for interaction with Ras-GTP and plasma membrane recruitment (BLOCK et al 1996;HSU et al 2002;HARDING et al 2003). We previously showed that transgenes expressing YFP-LIN-45(Q95A, R118A) fail to rescue the lin-45 null mutant, consistent with a loss of function (TOWNLEY et al 2023).…”
Section: Lin-45(s312a) Signaling Is Dependent On Ras and Ksr Activitymentioning
confidence: 85%
“…The BRAF DTS was initially proposed to positively regulate signaling; however, studies directly testing the effect of DTS truncation failed to show signaling differences (KONDO et al 2019;LIAU et al 2020a). A possible obstacle to testing the role of the BRAF DTS is that mammalian cells may express ARAF, BRAF, and RAF1 genes, and manipulations that inhibit one Raf can result in paradoxical activation of the pathway (HEIDORN et al 2010;POULIKAKOS et al 2010) The nematode Caenorhabditis elegans has a single Raf ortholog, termed LIN-45, that is required for larval viability, vulval fate specification, germline morphology, meiosis, and oocyte maturation (HAN et al 1993;HSU et al 2002). Phenotypes caused by lin-45 loss-of-function and gain-of-function during the process of vulval fate specification in larval development are easily observed later in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…As a negative regulator, we expect that ufd-2 loss would also suppress phenotypes resulting from reduced LIN-45 activity. We examined two alleles of lin-45 , termed n2018 and n2506 , that alter the LIN-45 RBD and result in partial loss of function and lethality at the L1 larval stage caused by failure of duct cell specification ( 23 , 24 ). Compared with either lin-45 loss-of-function mutant alone, the ufd-2(null); lin-45 double mutants displayed significantly reduced lethality (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If UFD-2 inhibits LIN-45 activity, then loss of ufd-2 may suppress phenotypes resulting from reduced LIN-45 activity. We examined two alleles of lin-45 that alter the LIN-45 RBD and result in partial loss of function and lethality at the L1 larval stage ( 22, 23 ). Compared to either lin-45 mutant alone, the ufd-2(0); lin-45 double mutants displayed a significant reduction in lethality (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We tested this by creating mutations at Q95 and R118 (Fig. S4), residues required for Ras-binding in vitro and LIN-45 function in vivo ( 23, 34 ). The mutant YFP-LIN-45(Q95A, R118A) was degraded in P6.pxx in wild type and stabilized in ufd-2(0) mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%